Can we rely on cancer mortality data? Checking the validity of cervical cancer mortality data for Slovenia - Primic-Žakelj, Maja (Radiology and oncology (Ljubljana), 2001)
Background. Valid inference on cervical cancer mortality is very difficult since - on the basis of death certificates - it is not always possible to distinguish between cervix, corpus and unspecified uterine cancer deaths. Our aim was to estimate the extent to which cervical cancer as the official cause of death reflects the true mortality from cervical cancer in Slovenia. Material and methods. The data on 2245 deaths from cervix, corpus uteri, and uterus-unspecified cancers for the period 1985-1999 were linked to the Cancer Registry of Slovenia database from the mortality database of Slovenia. Results. Officially, in the period 1985-1999, there were 878 cervical cancer deaths. The comparison of these causes of death with the cancer sites registered in the Cancer Registry revealed that they include only 87.7 % patients with a previous diagnosis of cervical cancer. Of 650 corpus uteri cancer deaths, 17.1% of patients were registered to have cervical cancer, and of 717 unspecified uterine cancer deaths, 31.4% were registered. Taking into account the correctly identified cervical cancer cases among cervical cancer deaths and misclassified cervical cancer deaths as corpus uteri and unspecified uterine, the corrected number of deaths would be 1106. Conclusions. When evaluating the impact of cervical cancer mortality from national mortality rates, the stated underestimation should be taken into account. However, this does not hold for some other cancers.
Keywords: Cerviks, novotvorbe; Cervix neoplasms; Death certificates; Maternica, novotvorbe; maternični vrat; mortaliteta; Mortality; rak (medicina); Registri; Registries; Smrt, potrdila; Uterine neoplasms